Peningkatan Keaktifan dalam Ibadah Melalui Metode Fish Bowl Di Kalangan Remaja Jemaat Gandangbatu, Tana Toraja - Febriani Upa' (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2021)
This study is an attempt to investigate the application of the fish bowl method in adolescent worship in the Toraja church, Gandang Batu congregation, South Sulawesi. This research uses a qualitative approach through literature study, observation and interviews (field research). The results showed that through the fish bowl method, the worshipers built intimacy with other teenagers. The character who used to be quiet and tended to close himself became an active and open child. Through this method they are taught to build cooperation, respect each other, accept others, motivate each other so as to create fun learning together. In addition, it is based on the admission from teenagers that they are more interested when the fish bowl method is used than the storytelling method. Through this method, each member is given the same opportunity to express their opinions and thoughts.